PENGUATAN KARAKTER INTEGRITAS DI SD MUHAMMADIYAH KADISOKA YOGYAKARTA PADA MASA PANDEMI - Suyitno Suyitno; Ardisa Pangestu Nur Waskito (Bhineka Tunggal Ika: Kajian Teori dan Praktik Pendidikan PKn, 2022)
Science and technology is now growing rapidly, causing concern both among educators and parents so that efforts are needed to instill and develop personality and character from an early age which are carried out in an integrated manner. This of course requires monitoring from various parties, such as formal institutions such as schools and informal institutions such as families (parents). This study aims to determine the strengthening of the character of integrity in SD Muhammadiyah Kadisoka Yogyakarta during the pandemic. This type of research uses qualitative research. The research method used is descriptive qualitative. This research was conducted at SD Muhammadiyah Kadisoka Yogyakarta with the research subject being the principal, curriculum representative, class teacher, parents of students, and students. Data collection techniques were in the form of observation, interviews and documentation. The results showed that 1) strengthening the character of integrity during the pandemic was carried out through daily activity books. 2) The teacher gives directions regarding the daily activity book as a guidebook during the pandemic. 3) Parents accompany and monitor children's activities while at home as outlined in the daily activity book. 4. Teachers and parents give rewards to students who are disciplined in filling out, collecting and carrying out daily activities and providing punishment for students who lie and are not responsible for carrying out daily activities.Keywords: Character Integrity, Elementary School, PandemiIPTEK kini berkembang dengan pesatnya sehingga menimbulkan kekhawatiran baik dikalangan pendidik maupun orang tua sehingga perlu upaya penanaman dan pembinaan kepribadian dan karakter sejak dini yang dilakukan secara terpadu. Hal ini tentunya membutuhkan pantauan dari berbagai pihak yakni seperti lembaga formal seperti sekolah dan informal seperti keluarga (orang tua). Penelitian ini bertujuan untuk mengetahui penguatan karakter integritas di SD Muhammadiyah Kadisoka Yogyakarta dimasa pandemi. Jenis Penelitian menggunakan penelitian kualitatif. Metode penelitian yang digunakan adalah deskriptif kualitatif. Penelitian ini dilaksanakan di SD Muhammadiyah Kadisoka Yogyakarta dengan subjek penelitian kepala sekolah, wakil kurikulum, guru kelas, orang tua peserta didik, serta peserta didik Teknik pengumpulan data berupa observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa 1) penguatan karakter integritas di masa pandemic dilakukan melalui buku kegiatan harian. 2) Guru memberi arahan mengenai buku kegiatan harian sebagai buku panduan selama pandemi. 3) Orang tua mendampingi dan memantau aktivitas anak selama di rumah yang dituangkan dalam buku kegiatan harian. 4. Guru dan Orang tua memberikan reward kepada peserta didik yang disiplin dalam mengisi, mengumpulkan dan melaksanakan kegiatan harian dan memberikan punishment bagi peserta didik yang berbohong dan tidak tanggungjawab dalam melaksanakan kegiatan harianKatakunci: Karakter Integritas, Sekolah Dasar, Pandemi